Life cycle assessment of biomethane use in Argentina - Morero, Betzabet del Valle (2015)
Renewable substitutes for natural gas, such as biogas, require adequate treatment to remove impurities. This paper presents the life cycle and environmental impact of upgrading biogas using absorption?desorption process with three different solvents: water, diglycolamine and polyethylene glycol dimethyl ether. The results showed that water produces a minor impact in most of the considered categories, and an economic analysis showed that water is the most feasible solvent for obtaining the lowest payback period. This analysis includes three different sources for biogas production and two end uses for biomethane. The use of different wastes as sources results in different environmental impacts depending on the type of energy used in the anaerobic digestion. The same situation occurs when considering the use of biomethane as a domestic fuel or for power generation. Using energy from biogas to replace conventional energy sources in production and upgrading biogas significantly reduce the environmental impacts of processes.